Record of Communication and Language Patterns among Social Media Users in Social Media Spaces: Content and Critical Discourse Analysis on Facebook Posts by Inside Lombok - Deki Zulkarnaen; Gita Sarwadi (Jurnal Ilmiah Mandala Education (JIME), 2025)
This study examines communication patterns and linguistic features used by social media users responding to three posts on the official Facebook account Inside Lombok, representing themes of public policy, local politics, and criminal law. Employing qualitative methods through content analysis and critical discourse analysis (CDA), fifteen comments (five per theme) were coded according to communication patterns, language features, and sentiment. The findings indicate a predominance of negative sentiment in political and criminal topics, whereas public policy topics elicited moree diverse responses, including constructive criticism and policy recommendations. The study contributes to the understanding of how local digital spaces function as arenas for contesting meaning, legitimacy, and public demands within digital political communication frameworks (Fairclough, 2021; van Dijk, 2020).